PERUBAHAN KANDUNGAN NUTRISI ASPARAGUS HIJAU (Asparagus officinalis L.) SELAMA PENYIMPANAN PADA SUHU DINGIN - Yana Putra Swija, I Nyoman; Sugitha, I Made; Trisna Darmayanti, Luh Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2015)
The aim of this study was to determine changes nutrients content of green Asparagus ( Asparagus officinalis L.) from Pelaga village at the time of harvest and during storage at cold temperatures. Completely Randomized Design (CRD) with single factor was used in this research. The factor was days of storage which consist of 9 level i.e.: 0, 3, 5, 7, 9, 11, 13, 15, and 17 days. The treatment repeated four times. The variables observed were moisture, ash, vitamin C, crude fiber, and sensory analysis (texture, visibility and overall acceptance). The result showed that the nutrition content of green asparagus decreased during storage 17 days. The decline occurred in the moisture content (93.90% (w / w) - 92.66% (w / w)), vitamin C (16.81 mg/100 g - 9.15 mg/100 g), crude fiber (2.03% - 0.29%) and sensory characteristics. Increasingly green asparagus stored, further decreased the nutritional content, as well as sensory characteristics. Green asparagus sensory is still acceptable for up to 9 days storage with water content of 93.12% w / w, ash content of 0.66%, vitamin C was 13.48 mg/100 g, and crude fiber by 0.57%.
Keywords: Green Asparagus, Storage, Nutrient Content